Feeding behavior of F1 Holstein x Zebu lactating cows fed increasing levels of banana peel - Paulo Roberto Silveira Pimentel; Vicente Ribeiro Rocha Júnior; Marco Túlio Parrela de Melo; Joyce Cipriana Pacheco Ramos; Lucas Gabriel Cardoso; Jéssica Jordane Pereira Silva (Acta Scientiarum. Animal Sciences, 2016)
This study evaluated the feeding behavior of F1 Holstein x Zebu cows fed increasing levels of banana peel. Diets contained 0, 15, 30, 45 and 60% replacement of sorghum silage with banana peel. The experimental design was two 5x5 Latin squares. Cows were subjected to visual observation after adaptation of each trial period. The times spent in feeding (4.13 to 5.58 hours day-1) and in idle (10 to 12.53 hours day-1) presented quadratic effect. The time spent ruminating, number and duration of rumination periods, chews per cud, and numbers of cuds per day were not affected by treatments. The total chewing time showed a quadratic effect, with peak at 18.58% replacement. The banana peel levels did not affect consumption, rumination and chewing neutral detergent fiber. Intake, rumination and chewing of dry matter showed a decreasing linear effect. The replacement of sorghum silage with banana peel up to 60% in the diet for lactating cows reduces the time spent in feeding and improves feeding and rumination efficiencies of dry matter, keeping the milk production of cows.